Evaluation of the Defay-Prigogine model for the membrane interphase in relation to biological response in membrane-protein interactions - Disalvo, Edgardo Anibal (2013)
Surface water activity appears as a common factor when the interaction of several aqueous soluble and surface active proteins with lipid membranes of different composition is measured by the changes in surface pressure of a lipid monolayer. The perturbation of the lipid surface caused by aqueous soluble proteins depends on the composition of the hydrocarbon phases, either modified by unsaturated bonds in the acyl chains or by inclusion of cholesterol. The cut-off (critical) surface pressure in monolayers, at which no effect of the proteins is found, is related to the composition of the head group region. The perturbation of surface pressure is produced by proteins when the area per lipid is above just 4% larger than that corresponding to the hydration shell of the phospholipid head groups found in the cut -off. This area excess gives place to regions in which the chemical potential of water changes with respect to bulk water. According to the Defay-Prigogine relation this interfacial water activity is the reason of the surface pressure increase induced by aqueous soluble proteins injected in the subphase. As predicted by solution chemistry, the increase of surface pressure is independent of the protein nature but depends on the water surface state determined by the lipid composition.